Field Testing Integrated Interventions for Schistosomiasis Elimination in the People's Republic of China: Outcomes of a Multifactorial Cluster-Randomized Controlled Trial - Williams, Gail M.; Li, Yue-Sheng; Gray, Darren J.; Zhao, Zheng-Yuan; Harn, Donald A.; Shollenberger, Lisa M.; Li, Sheng-Ming; Yu, Xinglin; Feng, Zeng; Guo, Jia-Gang; Zhou, Jie; Dong, Yu-Lan; et al. (Frontiers in Immunology, 2019)
Despite significant progress, China faces the challenge of re-emerging schistosomiasis transmission in currently controlled areas due, in part, to the presence of a range of animal reservoirs, notably water buffalo and cattle, which can harbour Schistosoma japonicum infections. Environmental, ecological and social-demographic changes in China, shown to affect the distribution of oncomelanid snails, can also impact future schistosomiasis transmission. In light of their importance in the S. japonicum, lifecycle, vaccination has been proposed as a means to reduce the excretion of eggs from cattle and buffalo, thereby interrupting transmission from these reservoir hosts to snails. A DNA-based vaccine (SjCTPI) our team developed showed encouraging efficacy against S. japonicum in Chinese water buffaloes. Here we report the results of a double-blind cluster randomised trial aimed at determining the impact of a combination of the SjCTPI bovine vaccine (given as a prime-boost regimen), human mass chemotherapy and snail control on the transmission of S. japonicum in 12 selected administrative villages around the Dongting Lake in Hunan province. The trial confirmed human praziquantel treatment is an effective intervention at the population level. Further, mollusciciding had an indirect ~50% efficacy on reducing human infection rates. Serology showed that the SjCTPI vaccine produced an effective antibody response in vaccinated bovines, resulting in a negative correlation with bovine egg counts observed at all post-vaccination time points. Despite these encouraging outcomes, the effect of the vaccine in preventing human infection was inconclusive. This was likely due to activities undertaken by the China National Schistosomiasis Control Program, notably the treatment, sacrifice or removal of bovines from trial villages, over which we had no control; as a result, the trial design was compromised, reducing power and contaminating outcome measures. This highlights the difficulties in undertaking field trials of this nature and magnitude, and emphasises the importance of mathematical modelling in predicting the potential impact of control intervention measures. A transmission blocking vaccine targeting bovines for the prevention of S. japonicum with the required protective efficacy would be invaluable in tandem with other preventive intervention measures if the goal of eliminating schistosomiasis from China is to become a reality.